Circulating adipokine levels and prognostic value in septic patients. Issue 1 (December 2016) - Hillenbrand, Andreas; Xu, Pengfei; Zhou, Shaoxia; Blatz, Annette; Weiss, Manfred; Hafner, Sebastian; Henne-Bruns, Doris; Knippschild, Uwe
Abstract Background Adipokines have a wide range of effects and are linked to sepsis and septic shock. The aim of the present study was to describe the changes in adipokine levels in septic patients in relation to patients' preseptic adipokine levels. Furthermore, we examined adipokines as prognostic markers. Methods Fourteen consecutive critically ill patients meeting the clinical criteria for severe sepsis or septic shock 3 days up to 1 month after major visceral surgery were enrolled prospectively. Plasma adipokines were measured preoperatively, 1 and 4 days after diagnosis of severe sepsis or septic shock following elective surgery. Results Median plasma adiponectin levels were lowered and resistin and leptin levels elevated in sepsis compared with preseptic plasma levels. MCP-1, C-reactive protein and white blood cell count were higher in septic compared with preseptic patients. Survivors had significantly higher preseptic adipokine levels than non-survivors. Adiponectin levels of survivors decreased significant (on average by 33 %) at day one after onset of sepsis compared with preseptic levels. In contrast, median adiponectin levels of patients dying during sepsis showed a slight increase (11 %). Median BMI of survivors was 30 kg/m2, median BMI of non-survivors was 25, respectively. Conclusions Adipokine levels change during the course of sepsis. Higher preseptic adiponectin levels and decreasing adiponectin levels after onset of sepsis are associated with survival of sepsis. Survival of overweight and obese patients was higher than in normal weight patients. Changes in adiponektin levels could be a prognostic marker for outcome of severe sepsis/septic shock following surgery.